Hypertensive Cardiogenic Shock in a Child with Acute Poststreptococcal Glomerulonephritis: An Unusual Presentation - A Case Report - Roy, Ranjit Ranjan; Akhter, Morsheda; Mamun, Abdullah Al; Rahman, Md. Azizur (Journal of Pediatric Nephrology, 2015)
A Acute poststreptococcal glomerulonephritis (APSGN) is one of the most common renal diseases resulting from a prior infection with group A β-hemolytic streptococcus. Manifestations of acute poststreptococcal glomerulonephritis ranges from subclinical infections to life threatening conditions. Typical clinical features of the disease include an acute onset with gross hematuria, edema, hypertension and moderate proteinuria (acute nephritic syndrome) 1 to 2 weeks after an antecedent streptococcal pharyngitis or 3 to 6 weeks after a streptococcal pyoderma. Patients with APSGN sometimes exhibit unusual clinical manifestations, which may lead to diagnostic delay or misdiagnosis of the disorder. Cardiogenic shock is uncommon but potentially fatal initial manifestations of ASPGN. There are very few reports of cardiogenic shock as the initial manifestation of APSGN. In patients presenting with cardiogenic shock, without a clear etiology, APSGN should be considered. We report a 07 year old boy presenting with cardiogenic shock as initial manifestations of APSGN. Keywords: Glomerulonephritis; Shock, Cardiogenic; Hypertension; Infections; Streptococcal.